Deciphering the microbiome potential and metabolic profiling of animal waste co-composting reveals the co-occurrence network of non-microbial and microbial biostimulants to strengthen conservative practices in sustainable agriculture - Argha Chakraborty; M. K. Saroja; Sourav Garai; Sukamal Sarkar; Aiswarya Bhattacharjee; Kalyan Roy; Sanchayeeta Misra; Rupak Goswami; Sudipta Tripathi; Natesan Ravisankar; Gautam Chatterjee (Chemical and Biological Technologies in Agriculture)
Abstract Background India has a rich history of agriculture with its vast biodiversity niches and traditional soil conservation practices. More recently, there have been growing molecular insights into crop-soil management practices and their niche microbial consortia and underlying services. However, harnessing traditional innovations to conserve and promote niche-specific microbiome management in agriculture has not been explored in detail. In an earlier report, we anticipated that the oldest documented microbial technology, Kunapajala, has the indigenous microbiome potential that reinforces its unifying cyclical operation interlinked with agro-waste recycling and valorization to eco-friendly food production. In the present study, we aimed to elucidate the molecular signatures of the microbiome–metabolite potential in this traditional liquid manure. Results Our results showed that fish- and livestock waste-derived Kunapajala are dynamic sources of plant-available macronutrients, plant growth regulators, and other bio-active compounds over 90 days of incubation. Besides estimation of microbial loads and dynamics in culture-based assays, whole genome metagenome (WGMG) sequencing data confirmed that bacteria, primarily Firmicutes and Proteobacteria, constitute the dominant kingdom (> 95% of total reads), with over 30% microbial abundance as potential plant growth-promoting rhizobacteria (PGPR), notably representing Clostridium, Corynebacterium, and Bacillus, in 30-day fermented products. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database further identifies the predominance of enzymatic regulations in carbohydrate and amino acid metabolism (> 20%), reflecting high organic matter turnover into different hydrolysates and metabolites in Kunapajala. To further support and validate, liquid chromatography coupled to hybrid quadrupole time-of-flight mass spectrometry (LC–QTOF-MS) based metabolite screening elucidates their potential roles in plant growth promotion and stress adaptation. We also investigate the plant biostimulant potential of Kunapajala and further establish its function as an organic fertilizer in a controlled pot-based assay in red amaranth. Overall, our microbiome–metabolite data highlight the dynamic co-occurrence of non-microbial and microbial biostimulants to redefine its niche compositional network and potential roles in sustainable agriculture. Conclusions Our study presents the first comprehensive microbiomes and metabolite profiling of Kunapajala, which could further advance and inform strategies for customized optimization of microbial consortia in agroecosystem functioning. Overall, employing metagenomic approaches to harnessing traditional organic amendments brings new molecular insights to strengthen conservative practices in sustainable agriculture. Graphical Abstract